2009
DOI: 10.1177/0146167209339783
|View full text |Cite
|
Sign up to set email alerts
|

And Yet They Move: The Impact of Direction of Deviance on Stereotype Change

Abstract: In 4 studies the authors compared the effect of exemplars that deviate from the prototype in one or the other direction while controlling for the absolute amount of deviance. Incongruent exemplars typically do not change a stereotype. Yet, it is unclear whether this is also the case with exemplars that are more extreme than the stereotype, named supercongruent hereafter. Within Study 1 the authors showed that supercongruent exemplars can be differentiated from congruent exemplars and that they are perceived as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…In line with this idea, Dolderer, Mummendey, and Rothermund (2009) found that information about outgroup members that was consistent with a negative group stereotype but even more extreme (i.e., less socially oriented and less helpful) was generalized to more negative views of the group stereotype. In contrast, stereotype-inconsistent information (i.e., more socially oriented and more helpful) did not affect the group stereotype.…”
Section: Negative Interpersonal Attitudes and Category Saliencementioning
confidence: 72%
“…In line with this idea, Dolderer, Mummendey, and Rothermund (2009) found that information about outgroup members that was consistent with a negative group stereotype but even more extreme (i.e., less socially oriented and less helpful) was generalized to more negative views of the group stereotype. In contrast, stereotype-inconsistent information (i.e., more socially oriented and more helpful) did not affect the group stereotype.…”
Section: Negative Interpersonal Attitudes and Category Saliencementioning
confidence: 72%
“…For instance, a number of studies found that exposure to Barack Obama at the time of the 2008 U.S. presidential election reduced anti-Black prejudice (Bernstein et al, 2010;Columb and Plant, 2011;Plant et al, 2009). However, attitude generalization can also result in more negative outgroup attitudes if the opinion about individual group members is negative (Dolderer et al, 2009). In fact, recent research has shown that students in school classes generalize positive and negative attitudes they have toward classmates from other ethnic groups to the same extent (Stark et al, 2013).…”
Section: Liking and Disliking Classmates Instead Of Contactmentioning
confidence: 99%
“…Castelli, Pavan, Ferrari, & Kashima, 2009;Dolderer, Mummendey, & Rothermund, 2009;Kashima, 2000;Plaks et al, 2001;Richards & Hewstone, 2001;Sherman, Stroessner, Conrey, & Azam, 2005;Vonk, 2002). The evidence for stereotypes' robustness to change is impressive.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%